Highly durable surface treatment of solid polymers

By using crosslinked acrylic resin or unsaturated polyester resin in solid surface materials and inorganic filler particles of specific particle size, combined with specific additives and components, the insufficient scratch resistance of solid surface materials in the prior art is solved. The problem has achieved the improvement of the durability of the material and the ability of woodworking.

CN119286174APending Publication Date: 2025-01-10DUPONT SAFETY & CONSTRUCTION INC
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411401737.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2017-07-07
Filing Date
2017-07-24
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

Existing solid surface materials have shortcomings in their scratch resistance and are difficult to maintain both carpentry and durability.

Method used

Inorganic filler particles with crosslinked acrylic resin or unsaturated polyester resin as the matrix and uniformly distributed on their surfaces is no more than 48 volume fraction percentages. The main size of the filler particles is between 0.5 and 10 microns, and D50 is 0.5. To 2.5 microns, D90 is less than 10 microns, combined with specific processing aids and components such as pigments, coupling agents, comonomers and crosslinkers to improve scratch resistance and repairability of the material.

Benefits of technology

The scratch resistance and repairability of solid surface materials are significantly improved, the durability and woodworking ability of the material are simultaneously improved, and the scratch perception and hardness are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

A highly durable surface treatment of solid polymers. The solid surface includes (i) a cross-linked acrylic or unsaturated polyester resin present in an amount of not more than 52 volume fraction percent, and (ii) not more than 48 volume fraction percent of inorganic filler particles uniformly distributed throughout the solid surface, wherein (a) 95-99 volume fraction percent of the filler particles have a major size of from 0.5 to not more than 10 microns, (b) the filler particles have a D50 of from 0.5 to 2.5 microns, and (c) the filler particles have a D90 equal to or less than 10 microns.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a divisional application of an invention patent application, the parent application of which is a Chinese patent application with an application date of July 24, 2017, application number 2017800770605 (PCT / US2017 / 043458), and invention name “Highly durable surface treatment of solid polymers”. Technical Field

[0002] The present invention relates to a highly durable solid surface useful in homes, medical buildings, hotels and restaurants. Background Art

[0003] The prior art describes techniques for imparting durability to material surfaces by including hard fillers or by applying hard coatings.

[0004] U.S. Pat. No. 5,800,910 to Harke et al. describes a plastic molded article comprising a polymer matrix filled with an inorganic filler, the filler content being 50 weight percent to 90 weight percent relative to the filled matrix, and the suggested filler comprises two filler parts (a) and (b), wherein the filler part (a) has the following particle size distribution, wherein 98 weight percent of the particles have a particle size of not more than 150 microns and are substantially uniformly distributed in the polymer matrix, and wherein the filler part (b) comprises particles having a particle size of approximately 300 microns to approximately 3000 microns, wherein the proportion of filler part (b) is approximately 1 weight percent to 35 weight percent of the total filler content, and wherein the proportion of filler part (b) in the outer surface layer of the molded article is enriched to at least 30 weight percent relative to the total mass of the filled matrix.

[0005] Japanese Patent Publication JP 2005126293 (A) by Kojima et al. discloses an artificial marble having excellent crack resistance and durability. The marble has a transparent layer on the surface of a base material comprising a thermosetting resin composition. The transparent layer contains a thermosetting resin and a filler and has a thickness of 1-5 mm.

[0006] Japanese Patent Publication JP 1991-174347 by Tanaka et al. teaches a shaped object comprising an acrylate resin binder and a metal hydroxide expander as 100 weight percent of a base resin, characterized in that the shaped object is obtained by adding and distributing 1 weight percent to 10 weight percent of a base resin, a powdered glass having a particle size distribution of 1 micron to 150 microns (having 10 weight percent to 30 weight percent of coarse grains having a particle size of 50 microns or more). The shaped object is preferably obtained by unevenly distributing coarse grained powdered glass on one surface side of the shaped object, and further, the powdered glass is a complex polygonal powder obtained by pulverization and has a new surface.

[0007] US Patent Application Publication No. 2015 / 0218343 to Rose et al. discloses a filler modified with functional particles by collisions of sufficient energy to bind, adhere, or otherwise associate the pigment particles to the filler during a high energy dry blending process.

[0008] U.S. Patent Application Publication No. 2015 / 0329706 to Rose et al. relates to a method for making a filled polymer material comprising a polymer matrix and a filler modified with functional particles by collisions of sufficient energy to bind, adhere, or otherwise associate pigment particles to the filler during a high energy dry blending process.

[0009] There remains a continuing need to provide enhanced durability for solid surfacing. The invention described herein improves the scratch resistance of solid surface materials, among other attributes, while maintaining their woodworking capabilities. The improved properties are inherent to the material and persist throughout the body of the article. Summary of the invention

[0010] The present invention relates to a solid surface comprising

[0011] (i) a cross-linked acrylic resin or an unsaturated polyester resin, present in an amount not greater than 52 volume percent, and

[0012] (ii) no more than 48 volume percent of inorganic filler particles uniformly distributed throughout the solid surface, wherein:

[0013] (a) 95-99 volume percent of the filler particles have a major dimension of 0.5 to no greater than 10 microns, or 1 to no greater than 5 microns, or 1 to no greater than 2 microns,

[0014] (b) the filler particles have a D50 of 0.5 to 2.5 microns, and

[0015] (c) The filler particles have a D90 of equal to or less than 10 microns. DETAILED DESCRIPTION

[0016] Solid Surface

[0017] Solid surface refers to a three-dimensional non-flexible rigid surface. Typically, the solid surface includes (i) 45 to 80 volume fraction percent of an organic polymer resin (typically polymethyl methacrylate or unsaturated polyester), and (ii) 25 to 55 volume fraction percent of inorganic filler particles uniformly distributed throughout the solid surface.

[0018] In one embodiment, the solid surface comprises

[0019] (i) a cross-linked acrylic resin or an unsaturated polyester resin, present in an amount not greater than 52 volume percent, and

[0020] (ii) no more than 48 volume percent of inorganic filler particles uniformly distributed throughout the solid surface, wherein:

[0021] (a) 95-99 volume percent of the filler particles have a major dimension of 0.5 to no greater than 10 microns, or 1 to no greater than 5 microns, or 1 to no greater than 2 microns,

[0022] (b) the filler particles have a D50 of 0.5 to 2.5 microns, and

[0023] (c) The filler particles have a D90 of equal to or less than 10 microns.

[0024] Organic polymer resin

[0025] One of the most common organic polymer resins is polymethyl methacrylate (PMMA) polymer or "acrylic" copolymer. PMMA is produced by the polymerization of an acrylic composition. The preparation of a polymerizable acrylic composition typically involves a slurry containing a methyl methacrylate polymer dissolved in the monomer methyl methacrylate (MMA) (also known as a polymer-in-monomer slurry), a polymerization initiator, and an inorganic filler. Such a composition and method of manufacture are disclosed in U.S. Pat. No. 3,847,865 to Duggins. The acrylic polymer component may further include a methyl methacrylate homopolymer and a copolymer of methyl methacrylate with other ethylenically unsaturated compounds such as vinyl acetate, styrene, alkyl acrylates, acrylonitrile, alkyl methacrylates, multifunctional acrylic monomers such as alkylene dimethacrylates and alkylene diacrylates. In addition, the polymer component may contain small amounts of other polymers, including small amounts of polyester or styrene polymers or copolymers.

[0026] Another common organic polymer resin is unsaturated polyester (UPE). UPE resins are composed of polyester polymers or copolymers that have covalently bonded unsaturation (such as carbon-carbon double bonds) incorporated, dissolved in a polymerizable styrenic monomer (such as styrene).

[0027] The resin composition can be cast or molded and cured to produce a sheet structure having an important combination of properties, including translucency, weatherability, resistance to staining by common household materials, flame resistance, and resistance to stress cracking. In addition, the cured article can be easily machined by conventional techniques, including sawing and sanding. This particular combination of properties makes such structures particularly useful as kitchen or bathroom countertops, splashbacks, wall coverings, molded articles such as towel racks, and the like.

[0028] Thermosetting resin

[0029] The above organic polymer resins are typically cross-linked, producing a polymer network known as a thermosetting resin. Key properties of thermosetting resins are strength retention at elevated temperatures and dimensional stability over time while being subjected to a variety of environmental conditions. Such properties make solid surface products desirable in homes and other buildings.

[0030] Fillers

[0031] "Filler" refers to any material, alone or in combination, that is solid at room temperature and atmospheric pressure, does not chemically react with the various ingredients of the composition and is insoluble in these ingredients, even when these ingredients are raised to a temperature above room temperature, and in particular to their softening point or their melting point. Preferred fillers are inorganic fillers.

[0032] In one embodiment, the inorganic filler particles are alumina trihydrate (ATH). Calcined ATH prepared by removing water through a thermal treatment process is also suitable.

[0033] In other embodiments, the inorganic filler particles are alumina, silica, talc, or quartz.

[0034] In another embodiment, the filler is a micronized organic polymer such as polyetheretherketone or polytetrafluoroethylene.

[0035] One means of characterizing particle size distribution (PSD) is D50, also known as the mass median diameter or median of the PSD. It is the weighted average diameter of particles with a normal or log-normal diameter distribution. Similarly, D90 is the diameter that accounts for 90% of the cumulative PSD.

[0036] At least 95 or 99 volume fraction percent of the filler particles have a major dimension of 0.5 to no greater than 10 microns, or 1 to no greater than 5 microns, or 1 to no greater than 2 microns. Within these ranges, the D50 is 0.5 to 2.5 microns, and the D90 is equal to or less than 10 microns. This size is much smaller than the particle size currently used in the industry, which has a D50 of about 10-50 microns and a D90 of sometimes greater than 100 microns.

[0037] The filler particles are evenly distributed throughout the solid surface, that is, their distribution is uniform throughout the bulk of the solid surface material. They are not merely present as a surface treatment layer.

[0038] Special processing aids

[0039] As with the properties of the particles in the mixture, those with small diameters impart high viscosity to the mixture. In some embodiments, a processing aid is added to the mixture to control viscosity. Examples of such processing aids can be found in U.S. Patent Application Publication No. 2008 / 0063850A1. The selection of processing aids is specific to the medium (e.g., acrylic resin, UPE resin), filler type and loading, and target viscosity range or desired flow behavior (e.g., shear thinning, Newtonian).

[0040] Other components of solid surfaces

[0041] The surface may further include additional components such as pigments, visible particles (including decorative particles), coupling agents, co-monomers or cross-linking agents.

[0042] Optionally, the solid surface material can contain aesthetic components, such as pigments or decorative particles. The term "pigment" refers to a colorant that is insoluble in the medium in which it is used, and therefore has particulate properties including its physical and chemical properties (e.g., surface charge and topology). The amount of pigment present is sufficient to provide the desired color effect, but typically 0.05 to 2.5 volume fraction percentage. The pigment can be added to the reactive mixture in powder form, but more commonly added as a suspension or dispersion in a carrier liquid. The solid surface material can also contain macroscopic decorative particles known in the industry as "chips". Chips are various filled and unfilled, colored or dyed, insoluble or cross-linked polymer fragments, such as ABS resins, cellulose esters, cellulose ethers, epoxy resins, polyethylene, ethylene copolymers, melamine resins, phenolic resins, polyacetals, polyacrylates, polydienes, polyesters, polyisobutylenes, polypropylene, polystyrene, urea / formaldehyde resins, polyureas, polyurethanes, polyvinyl chloride, polyvinylidene chloride, polyvinyl esters, etc. Other useful macroscopic translucent and transparent decorative particles are natural or synthetic minerals or materials, such as agate, alabaster, albite, calcite, chalcedony, flint, feldspar, flint quartz, glass, malachite, marble, mica, obsidian, opal, quartz, quartzite, rock gypsum, sand, silica, travertine, wollastonite, etc.; cloth, natural and synthetic fibers; and metal pieces.

[0043] The coupling agent enhances the performance characteristics of the solid surface material. Suitable coupling agents for the present invention are functionalized (meth) acrylates, such as 2-hydroxyethyl methacrylate or 3-(trimethoxysilyl)propyl methacrylate. These are typically present in an amount less than 1 volume fraction percentage. The coupling agent can be added to the reactive mixture or pre-applied to the filler surface. The coupling agent comonomer will copolymerize with the resin and bond to the filler surface.

[0044] Comonomers are usually introduced into organic polymer resins to change the performance characteristics of solid surface materials. A common example is n-butyl acrylate added to acrylic resins to enhance the thermal stability of solid surface materials. Comonomers are typically present in an amount of less than 2 volume fraction percent.

[0045] The crosslinking agent enhances the integrity of the article at high temperatures. Suitable acrylic crosslinking agents for use in the present invention are multifunctional (meth)acrylates, such as ethylene glycol dimethacrylate and trimethylolpropane trimethacrylate. In UPE resins, unsaturated polyesters are the main crosslinking agents.

[0046] It has been found that solid surfaces comprising ATH having a particle size as described above in a PMMA network or UPE resin are highly durable and easily repaired. This can be done simply by using an abrasive pad such as Scotch-BriteTM ) to be carried out. Such surfaces are sometimes called regenerable surfaces.

[0047] Method for manufacturing solid surface

[0048] Reproducible solid surfaces can be fabricated by the following steps:

[0049] (i) providing an uncured polymer composition comprising

[0050] (a) 0 to 15 volume percent PMMA,

[0051] (b) 10 to 40 volume percent of MMA,

[0052] (c) 1 to 50 volume percent of inorganic filler particles uniformly distributed throughout the solid surface, wherein at least 95 volume percent of the filler particles have a major dimension of 0.5 to no greater than 10 microns, or 1 to no greater than 5 microns, or 1 to no greater than 2 microns

[0053] (d) 0.1 to 2 volume percent of a curing agent.

[0054] (ii) pouring the composition of step (i) into a molded container, and

[0055] (iii) curing the composition at a temperature of between ambient and 80°C for between 3 and 60 minutes to allow the composition to solidify to form a solid surface.

[0056] In some embodiments, the inorganic filler is present in an amount of 15 to 50 volume percent.

[0057] Renewable unsaturated polyester or acrylic modified polyester solid surface can be made by the following steps:

[0058] (i) providing an uncured polymer composition comprising

[0059] (a) 0 to 15 volume percent PMMA,

[0060] (b) 10 to 40 volume percent of UPE resin,

[0061] (c) 1 to 50 volume percent of inorganic filler particles uniformly distributed throughout the solid surface, wherein at least 95 volume percent of the filler particles have a major dimension of 0.5 to no greater than 10 microns, or 1 to no greater than 5 microns, or 1 to no greater than 2 microns,

[0062] (d) 0.1 to 2 volume percent of a curing agent.

[0063] (ii) pouring the composition of step (i) into a molded container, and

[0064] (iii) curing the composition at a temperature of between ambient and 80°C for between 3 and 60 minutes to allow the composition to solidify to form a solid surface.

[0065] In some embodiments, the inorganic filler is present in an amount of 15 to 50 volume percent.

[0066] Test Method

[0067] Four-step scratch method

[0068] The scratch test used a micro scratch tester from CSM Instruments (Anton Paar) using a 1 mm alumina ball as the indenter. Before each experiment, the indenter was cleaned by sonication in reagent grade isopropanol for 30 minutes, in HPLC grade water for 30 minutes, and UV ozone treatment for 10 minutes. Before use, Zygo optical profilometry images were collected to qualify the indenter.

[0069] At least three separate scratches were made for each sample, and each scratch had four different load steps. In each case, three surface passes were made under controlled load. The first pass or pre-scan recorded the initial undamaged surface profile of the sample. During the second pass, the scratches were created with four load steps of 0.1, 10, 20 and 30 N. The scratches were 16 mm long, and a 4 mm section was used for each load step. After about 4 minutes, a third pass or post-scan was made to record the damage.

[0070] The penetration depth was calculated by subtracting the initial pre-scan profile from the displacement during the scratch. The residual depth was calculated by subtracting the post-scan displacement from the pre-scan. The pre-scan and post-scan were at a constant 0.1N load, which is below the plastic deformation threshold. The raw data from multiple scratches were combined and subjected to Anova calculations to statistically determine if there was an improvement in mechanical properties.

[0071] ASTM G171-03(2009) Standard Test Method for Scratch Hardness of Materials Using a Diamond Stylus

[0072] A hemispherical diamond tip is dragged across the surface with a controlled normal load. In the original ASTM method, an indenter with a 120 degree apex angle and a hemispherical tip with a 200 micron radius was specified. In our work, we used the Anton Paar microscratch test described above and an aluminum oxide sphere with a 1 mm diameter (500 micron radius). The scratch hardness is calculated by dividing the normal force during scratching by the projected area of ​​the indenter using the following formula:

[0073]

[0074] The normal load is in Newtons and the width of the scratch (2 x radius of contact area) is in meters, so the scratch hardness has units of pressure (in Pascals). Typical loads are a few Newtons. Dark field imaging is used to measure the scratch width at the center of each load step.

[0075] Scratch Visibility

[0076] There is no fundamental understanding of the relative importance of contrast versus size, but in existing work we use the following empirical formula to describe the visibility of scratches:

[0077]

[0078] As part of this project, a convenient way of measuring scratch visibility was developed and improved. Darkfield images from a conventional compound optical microscope combined with image processing give an accurate measure of both the average width and contrast level in different parts of the image.

[0079] Examples

[0080] The formulations in the examples are prepared using the following general procedures. Reactive organic resins are prepared in a reactor. In the case of acrylic acid products, typical reactive resins are composed of methyl methacrylate, methacrylate functionalized crosslinking agents, adhesion promoting comonomers, pigments, peroxides, and polymethyl methacrylate. Optionally, a curing rate accelerator may be included. In the case of unsaturated polyesters or acrylic acid-modified unsaturated polyesters, typical reactive resins are composed of unsaturated polyester polymers, styrene, peroxides, and curing rate accelerators. Optionally, acrylic polymers or copolymers may be included. The resin component is stirred vigorously, and then fillers are added to the mixture under continued stirring. Once the organic compound is homogenized and the mineral compound is well dispersed, the mixture is placed under vacuum. After the mixture is degassed, a peroxide accelerator is added to the stirred mixture. The activated mixture is then cast into an insulating mold, wherein the reactive mixture is cured and solidified.

[0081] Comparative Example 1

[0082] The reaction product produced a composite composed of 44.5 volume percent alumina trihydrate (WH311, 40 micron average particle size, Alcan), 55.5 volume percent thermosetting acrylic resin, and less than 1% white pigment (TiO2).

[0083] Example 1

[0084] The reaction product produced a composite composed of 40.5 volume percent alumina trihydrate (Hydral 710, 2 micron average particle size, JM Huber Corporation), 59.5 volume percent thermosetting acrylic resin, and less than 1% white pigment (TiO2).

[0085] Example 2

[0086] The reaction product produced a composite of 38.5 volume percent silane treated alumina trihydrate (Hymod 9400sc, 2 micron average particle size, treated with a methacrylate functionalized silane, Huber Group), 61.5 volume percent thermosetting acrylic resin, and less than 1% white pigment (TiO2). The adhesion promoting comonomer was omitted.

[0087] Comparative Example 2

[0088] The reaction product produced a composite composed of 44.5 volume percent alumina trihydrate (WH311, 40 micron average particle size, Alcan), 55.5 volume percent thermosetting acrylic resin, and less than 1% black pigment (carbon black).

[0089] Example 3

[0090] The reaction product produced a composite composed of 40.5 volume percent alumina trihydrate (Hydral 710, 2 micron average particle size, Huber Group), 59.5 volume percent thermosetting acrylic resin, and less than 1% black pigment (carbon black).

[0091] Compared to the comparative example having an ATH particle size of 35 microns, the inventive examples having a nominal ATH average particle size of 2 microns were found to show unexpected and surprising improved (lower) scratch visibility when subjected to a scratch force of 20 N. It is believed that the combination of particle size range and particle size distribution are essential elements to provide effective scratch resistance.

[0092] Measurement Comparative Example 1 Example #1 Example #2 Comparative Example 2 Example #3 Scratch Perception* 344 216 209 2390 611 Scratch hardness** / kPa 193 298 301 168 278

[0093] *Scratch perception is the product of visual contrast (i.e., the difference in average gray level between the unscratched surface and the center of the scratch) and the square root of the scratch width. Improvement is achieved by reducing scratch perception.

[0094] **Scratch hardness is calculated as described in ASTM G171-03 (2009). Improvement is achieved by increasing scratch hardness.

[0095] Comparative Example 3

[0096] The reaction product produced a composite consisting of 44.5 volume percent alumina trihydrate (WH311, 40 micron average particle size, Alcan), 55.5 volume percent unsaturated polyester resin (UPE resin, from Qualipoly Chemical Corporation, Kaohsiung, Taiwan, China), and less than 1% white pigment (TiO2).

[0097] Example 4

[0098] The reaction product produced a composite consisting of 40.5 volume percent alumina trihydrate (Hydral 710, 2 micron average particle size, Huber Group), 59.5 volume percent unsaturated polyester resin (UPE resin, from Kuo Jing Chemical Co., Ltd., Kaohsiung, Taiwan, China) and less than 1% white pigment (TiO2).

[0099] Comparative Example 4

[0100] The reaction product produced a composite consisting of 44.5 volume percent alumina trihydrate (WH311, 40 micron average particle size, Alcan), 55.5 volume percent unsaturated polyester resin (UPE resin, from Kuo Jing Chemical Co., Ltd., Kaohsiung, Taiwan, China) and less than 1% black pigment (carbon black).

[0101] Example 5

[0102] The reaction product produced a composite composed of 40.5 volume percent alumina trihydrate (Hydral 710, 2 micron average particle size, Huber Group), 59.5 volume percent unsaturated polyester resin (UPE resin, from Kuo Jing Chemical Co., Ltd., Kaohsiung, Taiwan, China) and less than 1% black pigment (carbon black).

[0103] Measurement Comparative Example 3 Example #4 Comparative Example 4 Example #5 Scratch Perception* 416 396 2509 1672 Scratch hardness** / kPa 125 146 120 141

[0104] *Scratch perception is the product of visual contrast (i.e., the difference in average gray level between the unscratched surface and the center of the scratch) and the square root of the scratch width. Improvement is achieved by reducing scratch perception.

[0105] **Scratch hardness is calculated as described in ASTM G171-03 (2009). Improvement is achieved by increasing scratch hardness.

Claims

1. A solid surface comprising (i) a cross-linked acrylic resin or an unsaturated polyester resin, which is present in an amount of 45 to 80 volume percent, and (ii) 15 to 50 volume percent of inorganic filler particles uniformly distributed throughout the solid surface, wherein (a) 95-99 volume percent of the filler particles have a major dimension of 0.5 to no greater than 10 microns, or 1 to no greater than 5 microns, or 1 to no greater than 2 microns, (b) the filler particles have a D50 of 0.5-2.5 microns, and (c) The filler particles have a D90 of equal to or less than 10 microns.

2. The surface of claim 1, wherein The filler types are alumina trihydrate, alumina, silica, talc or quartz.

3. The surface of claim 1, wherein The organic polymer component includes a coupling agent comonomer that will copolymerize with the resin and bond to the filler surface.

4. The surface of claim 1 further comprising decorative components such as pigments and / or visible particles.

5. The surface of claim 2, wherein: The filler particles are alumina trihydrate.

6. The surface of claim 1, wherein The cross-linked acrylic resin is a thermosetting acrylic resin.

Citation Information

Patent Citations

  • Molded body

    JP1991174347A

  • Artificial marble and its producing method

    JP2005126293A

  • Composition and process for producing acrylic composite materials with mineral charges having superior mechanical, thermal and processing properties

    US20080063850A1

  • Process for manufacturing coated filler particle

    US20150218343A1

  • Process for manufactuing filled polymeric materials with modified filler particles

    US20150329706A1